Dynamic availability of energy storage in district heating networks for automatic generation control of a CHP plant. (25th January 2021) - Deng, Tuoyu; Tian, Liang; Hu, Bo; Liu, Xinping; Liu, Jizhen; Zhou, Guiping; Zhao, Yuanzhu
Highlights: ES capacity is derived from first principles and described by a few parameters. Dynamic availability of ES is intuitively described by remaining time. ES calculation is fast and can meet 250 ms control cycle of CHP plant. Abstract: To increase power generation flexibility, combined heat and power (CHP) plant needs to improve automatic generation control (AGC) performance. A new approach to use energy storage (ES) in district heating networks (DHN) for AGC is proposed. First, the capacity of ES is analyzed quantitatively. By mechanism analysis of energy flow and conversion between DHN and CHP plant, the capacity and dynamic characteristics of ES in DHN is calculated quantitatively. The calculation result includes the maximum ES capacity and available time, the ES already used by CHP unit, and the remaining available ES and time. Second, basing on the quantitative analysis of ES, a control scheme is designed to make reasonable use of ES. The control scheme uses heat extraction valves as ES control variable and is designed basing on relative gain array method. Finally, a case study of a 330 MW CHP plant is given. The calculation results show that the maximum available time of ES in DHN is 2.85 h. And the simulation results show that the power generation increases by consuming ES in DHN and the AGC response is improved.